Verruciform xanthoma of buccal mucosa: A case report with review of literature - Sudhir Bhalerao; Pooja Bhat; Ranit Chhabra; Avinash Tamgadge (Wolters Kluwer Medknow Publications, 2012)
Verruciformxanthoma (VX) is an uncommon benign mucocutaneous lesion of unknown etiology. It appears as a papule or single plaque with verrucous or papillomatous surface and variable color from reddish pink to gray. It occurs primarily in the masticatory mucosa. Histologically, VX is characterized by the presence of parakeratinized epithelium with thin rete ridges and connective tissue papillae extending up to the surface. The papillae characteristically consist of foam cells, also called xanthoma cells. We report a case of VX in the buccal mucosa and discuss their clinical and histopathological findings.